The Sustainable Conflict Between Al Qur’an and Scientific Facts (Study of the Scientific Verses of Al Qur’an) - Mazaya Fuada; Ali Burhan (At Taawun Bangun Bangsa, 2026)
The relationship between the Qur’an and science has long been a subject of intellectual discourse, especially in areas such as cosmology, embryology, astronomy, geology, and ecology. The purpose of this research is to analyze Qur’anic verses alongside contemporary scientific findings in order to identify dimensions of harmony and potential conflict. The method applied is qualitative with a textual-analytical approach, combining classical tafsīr with modern scientific perspectives. The results indicate that the Qur’an provides theological and teleological insights rather than scientific explanations, while science offers methodological precision in exploring natural phenomena. Apparent contradictions emerge only when verses are interpreted literally or imposed into rigid scientific frameworks. The study concludes that the Qur’an and science can coexist within a paradigm of “sustainable conflict,” where tension is contextual and temporary, while Qur’anic guidance remains universal and timeless.